2005
DOI: 10.1111/j.1834-7819.2005.tb00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorders and oral health: A review of the literature

Abstract: This article is a review of the recent literature pertaining to the oral sequelae of eating disorders (EDs). Dentists are recognized as being some of the first health care professionals to whom a previously undiagnosed eating disorder patient (EDP) may present. However, despite the prevalence (up to 4 per cent) of such conditions in teenage girls and young adult females, there is relatively little published in the recent literature regarding the oral sequelae of EDs. This compares unfavourably with the attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
0
21

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 38 publications
(130 reference statements)
5
75
0
21
Order By: Relevance
“…Mais estudos são necessários em relação à sensibilidade orofaríngea em bulímicos, pois as fases oral e faríngea da deglutição podem estar alteradas secundariamente ao reconhecimento de características do alimento como volume, viscosidade e temperatura 15 . Ainda em relação à sensibilidade, a literatura menciona que indivíduos com uma longa história de bulimia tem um grande risco de desenvolver uma redução da sensibilidade gustativa (hipogeusia) 10,18,35 . Não há explicação clara para este achado, pois os estudos realizados não dividem os bulími-cos por método de compensação.…”
Section: Cavidade Oralunclassified
See 1 more Smart Citation
“…Mais estudos são necessários em relação à sensibilidade orofaríngea em bulímicos, pois as fases oral e faríngea da deglutição podem estar alteradas secundariamente ao reconhecimento de características do alimento como volume, viscosidade e temperatura 15 . Ainda em relação à sensibilidade, a literatura menciona que indivíduos com uma longa história de bulimia tem um grande risco de desenvolver uma redução da sensibilidade gustativa (hipogeusia) 10,18,35 . Não há explicação clara para este achado, pois os estudos realizados não dividem os bulími-cos por método de compensação.…”
Section: Cavidade Oralunclassified
“…A etiologia da queilite angular também está associada à presença do fungo Candida albicans 35 . Nota-se, portanto, que tais achados podem estar associados até mesmo às queixas na fase preparatória oral da deglutição.…”
Section: Cavidade Oralunclassified
“…The prevalence of eating disorders is 36.5% and women are the most affected 6 . The etiology of major eating disorders, anorexia and bulimia nervosa, is unknown and they are characterized by abnormal eating patterns and weight control, as well as changes in body perception and weight 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The studies revealed erosive lesions to appear more often in anorectic patients (with restrictive anorexia) than in bulimic ones or those with bulimic anorexia, i.e. in those patients who vomit, but at the same time more often than in healthy individuals [14,16,31].…”
mentioning
confidence: 99%
“…Thirst following exercise is often quenched with energy or isotonic drinks of low pH (below 3.0) [16,23]. The location of non-carious lesions is due to a specific etiological factor, such as vomiting, dietary or hygienic habits [16,31]. The studies revealed erosive lesions to appear more often in anorectic patients (with restrictive anorexia) than in bulimic ones or those with bulimic anorexia, i.e.…”
mentioning
confidence: 99%